2021
DOI: 10.1071/wr21002
|View full text |Cite
|
Sign up to set email alerts
|

Using lures for improving selectivity of bait intake by red foxes

Abstract: Context The use of baits for reducing the populations of harmful animal species, eradicating invasive species, vaccination, contraception or producing conditioned aversion, is widespread worldwide. However, baiting programs are often not successful enough and affect non-target species, requiring new approaches for baiting methods. Aims The aim of the present study was to evaluate two attractants used in carnivore studies to improve bait intake probability by red foxes and minimise bait intake by non-target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The captivity tests were carried out in over a period of twenty days in February 2022 at Sendaviva zoological park located in Arguedas, province of Navarra, Northern Spain, where six wolves were kept in the same enclosure spanning approximately one hectare. We tested the following five attractants on the basis of previous studies with wolves and other carnivores: (1) a commercial concentrated beef extract (Bovril®; Roche 2008); (2) cadaverine, an own elaboration water solution of rotten fish (Avrin et al 2021;Jiménez et al 2023); (3) FAS containing a mixture of ten synthetic volatile fatty acids found in fermented egg (Roughton 1982;Monterroso et al 2011;Tobajas et al 2022) that is commonly used as a generalist carnivore attractant in North America (Roughton and Sweeny 1982); (4) lynx urine (obtained from captive specimens of Iberian lynx (Lynx pardinus), Monterroso et al 2011;Tobajas et al 2022); and (5) valerian-extract solution containing valeric acid found in urine and anal-sac secretions of coyote (Canis latrans) and red fox (Saunders and Harris 2000;Ferreras et al 2018). The six Iberian wolves were adults (four females and two males) and they had access to the attractants 24 h a day, as they were in the same enclosure as the wolves, during the 20 days of experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The captivity tests were carried out in over a period of twenty days in February 2022 at Sendaviva zoological park located in Arguedas, province of Navarra, Northern Spain, where six wolves were kept in the same enclosure spanning approximately one hectare. We tested the following five attractants on the basis of previous studies with wolves and other carnivores: (1) a commercial concentrated beef extract (Bovril®; Roche 2008); (2) cadaverine, an own elaboration water solution of rotten fish (Avrin et al 2021;Jiménez et al 2023); (3) FAS containing a mixture of ten synthetic volatile fatty acids found in fermented egg (Roughton 1982;Monterroso et al 2011;Tobajas et al 2022) that is commonly used as a generalist carnivore attractant in North America (Roughton and Sweeny 1982); (4) lynx urine (obtained from captive specimens of Iberian lynx (Lynx pardinus), Monterroso et al 2011;Tobajas et al 2022); and (5) valerian-extract solution containing valeric acid found in urine and anal-sac secretions of coyote (Canis latrans) and red fox (Saunders and Harris 2000;Ferreras et al 2018). The six Iberian wolves were adults (four females and two males) and they had access to the attractants 24 h a day, as they were in the same enclosure as the wolves, during the 20 days of experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Attractants for carnivores can be classified in three groups based on their characteristics: (i) natural attractants, which are naturally occurring in the environment with communicative function as faeces, gland secretions or urine; (ii) baits, typically consisting of food or its derivates, which are intended to be consumed and attract animals through smell or taste; and (iii) lures, which are substances that are not naturally present in the environment and attract animals through smell, sound or sight (Schlexer 2008). The use of these attractants improves the detectability, or even the selectivity of the target species (Steyer et al 2013;Ferreras et al 2018;Tobajas et al 2022), increasing the cost-effectiveness of the surveys, especially in areas of expansion with low abundances (Ferreras et al 2017;Buyaskas et al 2020). This is especially relevant in cases such as large carnivore surveys, where the large home ranges imply high sampling and economic efforts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a project to protect California condor (Gymnogyps californianus) eggs from ravens (Corvus corax) showed that the condor itself was most likely to be affected by the intervention, but could be safely protected with the compound landrin (Quick and Hill, 1988). Further, research should explore use of selective bait deployment methods to reduce ingestion by non-target animals and the smart use of lures or attractants to increase the food detectability specifically by the target species (Ferreras et al, 2018;Tobajas et al, 2021b). Another way to avoid bait consumption by nontarget species is to directly inject the substance into the subject after it has eaten the relevant food.…”
Section: Animal Safetymentioning
confidence: 99%